2020
DOI: 10.5664/jcsm.8758
|View full text |Cite
|
Sign up to set email alerts
|

Dream enactment behavior—a real nightmare: a review of post-traumatic stress disorder, REM sleep behavior disorder, and trauma-associated sleep disorder

Abstract: Dream enactment behavior is a phenomenon demonstrated in patients with post-traumatic stress disorder, rapid eye movement sleep behavior disorder, as well as with a more recently described condition entitled trauma-associated sleep disorder, which shares diagnostic criteria for rapid eye movement sleep behavior disorder. While these conditions share some commonalities, namely dream enactment behavior, they are quite different in pathophysiology and underlying mechanisms. This review will focus on these 3 condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…We noted that the global population was suffering from a relatively high level of anxiety, depression, and PTSD symptoms during the COVID‐19 pandemic (Morin et al, 2021 ; Salari et al, 2020 ), which might have been associated with an abundance of distress that may culminate into the development of parasomnia (Barone, 2020 ). Previous studies suggested that parasomnia including RBD is common among the psychiatric population (Lam, Fong, Ho, Yu, & Wing, 2008 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We noted that the global population was suffering from a relatively high level of anxiety, depression, and PTSD symptoms during the COVID‐19 pandemic (Morin et al, 2021 ; Salari et al, 2020 ), which might have been associated with an abundance of distress that may culminate into the development of parasomnia (Barone, 2020 ). Previous studies suggested that parasomnia including RBD is common among the psychiatric population (Lam, Fong, Ho, Yu, & Wing, 2008 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, they could be related to the emotional impact denoted by increased anxiety and depression symptoms during MSI stressful conditions. The necessity of characterizing the phenomenology of dream enacting behaviors had been pointed out by two recent and excellent reviews 64 , 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in those veterans with RWA, RBD appeared related to PTSD (prevalence rate 15%) and even more so to the combination of PTSD and traumatic brain injury (prevalence rate 21%). Therefore, it is still controversial whether TASD really represents a separate sleep disorder ( 17 , 18 ).…”
Section: Ptsd and Sleep Disturbancesmentioning
confidence: 99%